Elemental composition and mineralogical characteristics of volcanic ash and soil affected by the eruption of Mount Semeru, East Java - Setiawati, Tri Candra; Nurcholis, Mohammad; Basuki, Basuki; Budiman, Subhan Arif; Yudiantoro, Dwi Fitri (Brawijaya University, 2024)
The eruption of Mount Semeru at the end of 2021 was responsible for emitting volcanic ash with specific characteristics. These unique mineralogy and chemical properties have both positive and negative effects on soil fertility, as excessive heavy metals adversely affect soil, plants, and the environment. Therefore, this study aimed to determine the distribution of volcanic ash cover from the eruption of Mount Semeru and investigate elemental composition as well as mineral characteristics of volcanic ash and soil covered by volcanic ash. The investigation was carried out in Supiturang village, Pronojiwo District, Lumajang, East Java, Indonesia. Sampling was carried out following the toposequence method, covering agricultural land within approximately ± 15 km from Mount Semeru. Pure volcanic ash was collected at sites not contaminated with soil. At the site location, it was found that the depth of volcanic ash cover ranged from “thin” (<2 cm) to “very thick” (>10 cm). The results of SEM and XRD analyses showed that of the pure volcanic ash contained quartz (50%), rock fragments (15%), plagioclase (12%), hornblende (10%), opaque (8%), and pyroxene (5%) minerals. The results of XRF analysis showed that the dominant elements in volcanic ash and soil were silica (Si), aluminum (Al), calcium (Ca), iron (Fe), and potassium (K). Several non-essential heavy metal elements found were Pb, Sn, and As, while rare minerals discovered were Y, Nb, Eu, and Yb at relatively low concentrations. The SEM analysis showed the structure of volcanic ash dominated by prismatic and blocky.